Perinatal outcomes of quadruplet pregnancy - S. A. Kalashnikov; D. R. Kudratova (Акушерство, гинекология и репродукция, 2021)
Introduction. A significantly increased frequency of multiple pregnancies including more than two fetuses is a consequence of using assisted reproductive technologies and ovulation stimulations. However, such pregnancies remain poorly investigated. Aim: to study the course and perinatal outcomes of quadruplet pregnancies.Materials and Methods. 7 pregnant women with quadruplets were examined. A comprehensive examination, including fetometry, monitoring of the cervical length, Doppler examination, and treatment of all complications were performed for all pregnant women. Results. Quadruplet pregnancy belongs to the peak risk group for the frequency of multiple gestational complications: cervical incompetence (85.7 %), anemia (71.4 %), preeclampsia (57.1 %), fetal growth retardation (71.4 %), premature birth (100.0 %), massive bleeding during delivery (33.3 %), extremely low birth weight newborns (30.8 %), respiratory disorders (100.0 %), intraventricular hemorrhages (38.5 %).Conclusion. Women with quadruplet pregnancies should be monitored and give a birth in level 3 perinatal centers. Delivery should be preferentially performed by caesarean section. The data obtained additionally underline that as few as a single embryo should solely transferred.